Dietary Oregano Oil Supplementation Improved Egg Quality by Altering Cecal Microbiota Function in Laying Hens - Lili Xian; Yan Wang; Da Peng; Lei Zang; Yidan Xu; Yuanyuan Wu; Jingjing Li; Jing Feng (Animals)
Improving egg quality is one of the main objectives of the poultry industry. The objective of this study was to investigate the effects of dietary oregano oil supplementation with different concentrations on the egg quality, intestinal morphology and cecal microbiome of late-phase laying hens. A total of 300 55-week-old Snowy white laying hens were randomly divided into five groups and fed a basal diet (control) or basal diets supplemented with oregano oil at 25, 50, 75 and 100 mg/kg (O25, O50, O75 and O100) over a 100-day period. Compared with the control group, eggshell thickness and eggshell weight were increased significantly in eggs when oregano oil was added (p < 0.05). The highest content of polyunsaturated fatty acids (PUFAs) and C18:2n6c was observed in yolks with 25 mg/kg supplement among 5 groups (p < 0.05). The highest average content of riboflavin in egg yolk and thiamine in egg white was observed in the O25 group (p < 0.05). When the supplemental levels of oregano oil were 25 mg/kg and 50 mg/kg, the selenium and phosphorus content in the egg was significantly increased (p < 0.05). The ratio of villus height to crypt depth (V/C) and villus height of the small intestine was significantly increased compared with the chickens fed the basal diet (p < 0.05). Compared with the control group, the abundance of Megamonas was increased in the O50 group (p < 0.05). The unclassified_o__Bacteroidales in the O25 group were significantly higher than those in the other four groups (p < 0.05). These differential microorganisms were significantly correlated with egg quality characteristics. Dietary supplementation of oregano oil can significantly improve egg quality via gut microbiota alteration in laying hens.